Zig-Zag Running Training's Impact on Dribbling Speed - Veni Suryani; Dessy Wardiah; Siti Ayu Risma Putri; Putri Cicilia Kristina; Sugarwanto Sugarwanto (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The primary objective of this study is to investigate the potential impact of zig-zag running training on the dribbling speed of basketball extracurricular students enrolled at SMP Negeri 1 Bunga Mayang OKU Timur. The study aims to analyze whether this particular training technique can improve the students' dribbling speed, which is a crucial skill in basketball. The study will collect data from a sample of students and analyze the results to conclude the effectiveness of zig-zag running training on dribbling speed. Materials and methods. This is descriptive quantitative research that uses data analysis techniques to measure instruments or tests. The research employs T-test statistical data to conduct normality and hypothesis tests. The research subjects are students participating in basketball extracurricular activities at SMP Negeri 1 Bunga Mayang. Results. According to the analysis of the research data, the value of t_table is 1.860. This value has been obtained from the t distribution with dk (10-2) = 8 and α=0.05, as listed in the table. The hypothesis testing criteria indicate that if t_count > t_table, the Hα hypothesis is accepted, and if Ho t_count < t_tabel, it is rejected. The t_count value in this case is 14.09, which is greater than the t_table value of 1.860. Therefore, we can conclude that there is a significant difference between the pre-test and post-test. Conclusion. After conducting the necessary tests and analysis, it has been found that the Ho hypothesis, which stated that there is no significant influence of zig-zag running training on dribbling speed in basketball extracurricular students at SMP Negeri 1 Bunga Mayang OKU Timur, is not supported by the data. On the other hand, the Hα hypothesis, which states that there is an influence of zig-zag running training on dribbling speed in the same group of students, has been confirmed by the results of the study. Therefore, it can be concluded that the zig-zag running training has a positive impact on the dribbling speed of basketball extracurricular students at SMP Negeri 1 Bunga Mayang OKU Timur.